2018
DOI: 10.1021/acs.est.7b04576
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Connected and Automated Vehicles: Sensing and Computing Subsystem and Vehicle Level Effects

Abstract: Although recent studies of connected and automated vehicles (CAVs) have begun to explore the potential energy and greenhouse gas (GHG) emission impacts from an operational perspective, little is known about how the full life cycle of the vehicle will be impacted. We report the results of a life cycle assessment (LCA) of Level 4 CAV sensing and computing subsystems integrated into internal combustion engine vehicle (ICEV) and battery electric vehicle (BEV) platforms. The results indicate that CAV subsystems cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(111 citation statements)
references
References 13 publications
2
109
0
Order By: Relevance
“…Life cycle approaches have been used extensively to address comparable questions for other transportation technologies. For example, other studies have examined alternative transportation options, including electric vehicles [3,4], car-sharing programs [5], autonomous vehicles [6], and electric bicycles [7,8], as well as full urban transportation systems [9] and comparisons across two-wheel vehicles [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Life cycle approaches have been used extensively to address comparable questions for other transportation technologies. For example, other studies have examined alternative transportation options, including electric vehicles [3,4], car-sharing programs [5], autonomous vehicles [6], and electric bicycles [7,8], as well as full urban transportation systems [9] and comparisons across two-wheel vehicles [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For battery electric vehicles, which are considered important mitigation technologies within the transport sector [1], studies have found that battery production is an energy-consuming process that offsets some of the efficiency gains of electric motors over internal combustion engines [120]. Similarly, the production and operation of information and communication technology (ICT) systems may substantially offset the benefits from automated driving, platooning and other energy-saving operations that are enabled by these ICT systems [121,122]. Car ownership is often seen as a hallmark of the middle class [123] and has been rising quickly in emerging economies.…”
Section: Me In Vehiclesmentioning
confidence: 99%
“…Through trip-chaining, autonomous taxis (ATs) could radically reduce the number of vehicles required, potentially at the cost of increased vehicle turn-over and longer distances. Other environmental effects arise from the easier electrification of the fleet, the higher initial energy and material requirements of ATs, the issue of empty trips, and benefits through eco-driving and platooning [121,122,136]. The impact of ATs, carsharing and ride-hailing on overall travel demand seems to be inconclusive and may depend on many local factors.…”
Section: Me In Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, EVs are best suited to reduce emissions in the sector and therefore help meet policy targets. Specifically in this case, it is suggested that autonomous EVs produce dramatically fewer emissions than gasoline AVs (Gawron et al, 2018) and consume fewer energy (Vahidi and Sciarretta, 2018). Third, EVs are technically and economically beneficial rather for longer daily travel distances experienced by shared fleets due to their relatively low maintenance needs (Logtenberg et al, 2018;Palmer et al, 2018;Weldon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%